Diabetes Mellitus Prediction on Obese Adult Ladies Using Data Mining Techniques - Thomas, Manumol; Chandra, J (International Journal of Computer Sciences and Engineering, 2025)
The research deals with prediction of Diabetes Mellitus in Pregnant and Non pregnant obese adult ladies using the data mining classification algorithms such as J48, Naïve Bayes, and SVM. Comparative study of classification algorithm is done by using Naïve Bayes, J48 and SVM. The results obtained by J48 and Naïve Bayes were found to be more satisfactory when compared to SVM classification. Naïve Bayes and J48 can be used as a predictor classifier for doing the diabetes mellitus prediction.